Trask - Berry, Don (Book collections on Project MUSE., 2004)
"Set in 1848 on the wild edge of the continent, in the rainforests and rugged headlands of the Oregon coast, Trask follows a mountain man's quest for new opportunities and new land to settle. Elbridge Trask is a restless man, a gambler with God, nature, and life itself. Yearning for change, he sets out with Wakila, a young Clatsop Indian, and Charley Kehwa, a tamanawis man or spiritual leader of the tribe, on an extraordinary journey of discovery."--Jacket.